Do Japanese companies transfer their recruitment and training culture abroad? : The case of Germany - Dellori, Julia [Verfasser]; Pilz, Matthias [Verfasser] (My University, 2026)
„A significant number of Japanese multinational companies operate in Germany and require a skilled work force. Recruitment and training in particular, as part of human resource management, are often heavily influenced by practices from their home county. This raises the question of how assertive Japanese recruitment and training practices are within the German context, where the unique dual training system is of particular importance. This study therefore examines standardisation effects (the consistency of practices within an organisation across national borders) in recruitment and training in Japanese subsidiaries in Germany. The findings, based on 21 expert interviews, indicate a standardisation with regard to Japanese practices. The study reveals a strong influence on both recruitment and training within the companies studied, particularly in domains where German regulations and laws exert minimal influence. However, different types of standardisation effects emerge for distinct practices. The analysis suggests a classification into three types of standardisation, based on the degree of consistency between practices in the host and home countries, allowing for a more nuanced understanding of standardisation effects. These findings contribute to an extension of the theoretical foundations in this field.“ (authors’ abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; S 5.3 Personalentwicklung; I 2.3.4 Asien; 370; Unternehmen; Internationales Unternehmen; Personalmanagement; Personalgewinnung; Berufsausbildung; Standardisierung; Interview; Bundesrepublik Deutschland; Japan